Theory RingHom
theory RingHom
imports Ideal
begin
section ‹Homomorphisms of Non-Commutative Rings›
text ‹Lifting existing lemmas in a ‹ring_hom_ring› locale›
locale ring_hom_ring = R?: ring R + S?: ring S
for R (structure) and S (structure) +
fixes h
assumes homh: "h ∈ ring_hom R S"
notes hom_mult [simp] = ring_hom_mult [OF homh]
and hom_one [simp] = ring_hom_one [OF homh]
sublocale ring_hom_cring ⊆ ring: ring_hom_ring
by standard (rule homh)
sublocale ring_hom_ring ⊆ abelian_group?: abelian_group_hom R S
proof
show "h ∈ hom (add_monoid R) (add_monoid S)"
using homh by (simp add: hom_def ring_hom_def)
qed
lemma (in ring_hom_ring) is_ring_hom_ring:
"ring_hom_ring R S h"
by (rule ring_hom_ring_axioms)
lemma ring_hom_ringI:
fixes R (structure) and S (structure)
assumes "ring R" "ring S"
assumes hom_closed: "!!x. x ∈ carrier R ==> h x ∈ carrier S"
and compatible_mult: "⋀x y. [| x ∈ carrier R; y ∈ carrier R |] ==> h (x ⊗ y) = h x ⊗⇘S⇙ h y"
and compatible_add: "⋀x y. [| x ∈ carrier R; y ∈ carrier R |] ==> h (x ⊕ y) = h x ⊕⇘S⇙ h y"
and compatible_one: "h 𝟭 = 𝟭⇘S⇙"
shows "ring_hom_ring R S h"
proof -
interpret ring R by fact
interpret ring S by fact
show ?thesis
proof
show "h ∈ ring_hom R S"
unfolding ring_hom_def
by (auto simp: compatible_mult compatible_add compatible_one hom_closed)
qed
qed
lemma ring_hom_ringI2:
assumes "ring R" "ring S"
assumes h: "h ∈ ring_hom R S"
shows "ring_hom_ring R S h"
proof -
interpret R: ring R by fact
interpret S: ring S by fact
show ?thesis
proof
show "h ∈ ring_hom R S"
using h .
qed
qed
lemma ring_hom_ringI3:
fixes R (structure) and S (structure)
assumes "abelian_group_hom R S h" "ring R" "ring S"
assumes compatible_mult: "⋀x y. [| x ∈ carrier R; y ∈ carrier R |] ==> h (x ⊗ y) = h x ⊗⇘S⇙ h y"
and compatible_one: "h 𝟭 = 𝟭⇘S⇙"
shows "ring_hom_ring R S h"
proof -
interpret abelian_group_hom R S h by fact
interpret R: ring R by fact
interpret S: ring S by fact
show ?thesis
proof
show "h ∈ ring_hom R S"
unfolding ring_hom_def by (auto simp: compatible_one compatible_mult)
qed
qed
lemma ring_hom_cringI:
assumes "ring_hom_ring R S h" "cring R" "cring S"
shows "ring_hom_cring R S h"
proof -
interpret ring_hom_ring R S h by fact
interpret R: cring R by fact
interpret S: cring S by fact
show ?thesis
proof
show "h ∈ ring_hom R S"
by (simp add: homh)
qed
qed
subsection ‹The Kernel of a Ring Homomorphism›
lemma (in ring_hom_ring) kernel_is_ideal: "ideal (a_kernel R S h) R"
apply (rule idealI [OF R.ring_axioms])
apply (rule additive_subgroup.a_subgroup[OF additive_subgroup_a_kernel])
apply (auto simp: a_kernel_def')
done
text ‹Elements of the kernel are mapped to zero›
lemma (in abelian_group_hom) kernel_zero [simp]:
"i ∈ a_kernel R S h ⟹ h i = 𝟬⇘S⇙"
by (simp add: a_kernel_defs)
subsection ‹Cosets›
text ‹Cosets of the kernel correspond to the elements of the image of the homomorphism›
lemma (in ring_hom_ring) rcos_imp_homeq:
assumes acarr: "a ∈ carrier R"
and xrcos: "x ∈ a_kernel R S h +> a"
shows "h x = h a"
proof -
interpret ideal "a_kernel R S h" "R" by (rule kernel_is_ideal)
from xrcos
have "∃i ∈ a_kernel R S h. x = i ⊕ a" by (simp add: a_r_coset_defs)
from this obtain i
where iker: "i ∈ a_kernel R S h"
and x: "x = i ⊕ a"
by fast+
note carr = acarr iker[THEN a_Hcarr]
from x
have "h x = h (i ⊕ a)" by simp
also from carr
have "… = h i ⊕⇘S⇙ h a" by simp
also from iker
have "… = 𝟬⇘S⇙ ⊕⇘S⇙ h a" by simp
also from carr
have "… = h a" by simp
finally
show "h x = h a" .
qed
lemma (in ring_hom_ring) homeq_imp_rcos:
assumes acarr: "a ∈ carrier R"
and xcarr: "x ∈ carrier R"
and hx: "h x = h a"
shows "x ∈ a_kernel R S h +> a"
proof -
interpret ideal "a_kernel R S h" "R" by (rule kernel_is_ideal)
note carr = acarr xcarr
note hcarr = acarr[THEN hom_closed] xcarr[THEN hom_closed]
from hx and hcarr
have a: "h x ⊕⇘S⇙ ⊖⇘S⇙h a = 𝟬⇘S⇙" by algebra
from carr
have "h x ⊕⇘S⇙ ⊖⇘S⇙h a = h (x ⊕ ⊖a)" by simp
from a and this
have b: "h (x ⊕ ⊖a) = 𝟬⇘S⇙" by simp
from carr have "x ⊕ ⊖a ∈ carrier R" by simp
from this and b
have "x ⊕ ⊖a ∈ a_kernel R S h"
unfolding a_kernel_def'
by fast
from this and carr
show "x ∈ a_kernel R S h +> a" by (simp add: a_rcos_module_rev)
qed
corollary (in ring_hom_ring) rcos_eq_homeq:
assumes acarr: "a ∈ carrier R"
shows "(a_kernel R S h) +> a = {x ∈ carrier R. h x = h a}"
proof -
interpret ideal "a_kernel R S h" "R" by (rule kernel_is_ideal)
show ?thesis
using assms by (auto simp: intro: homeq_imp_rcos rcos_imp_homeq a_elemrcos_carrier)
qed
lemma (in ring_hom_ring) hom_nat_pow:
"x ∈ carrier R ⟹ h (x [^] (n :: nat)) = (h x) [^]⇘S⇙ n"
by (induct n) (auto)
lemma (in ring_hom_ring) inj_on_domain:
assumes "inj_on h (carrier R)"
shows "domain S ⟹ domain R"
proof -
assume A: "domain S" show "domain R"
proof
have "h 𝟭 = 𝟭⇘S⇙ ∧ h 𝟬 = 𝟬⇘S⇙" by simp
hence "h 𝟭 ≠ h 𝟬"
using domain.one_not_zero[OF A] by simp
thus "𝟭 ≠ 𝟬"
using assms unfolding inj_on_def by fastforce
next
fix a b
assume a: "a ∈ carrier R"
and b: "b ∈ carrier R"
have "h (a ⊗ b) = (h a) ⊗⇘S⇙ (h b)" by (simp add: a b)
also have " ... = (h b) ⊗⇘S⇙ (h a)" using a b A cringE(1)[of S]
by (simp add: cring.cring_simprules(14) domain_def)
also have " ... = h (b ⊗ a)" by (simp add: a b)
finally have "h (a ⊗ b) = h (b ⊗ a)" .
thus "a ⊗ b = b ⊗ a"
using assms a b unfolding inj_on_def by simp
assume ab: "a ⊗ b = 𝟬"
hence "h (a ⊗ b) = 𝟬⇘S⇙" by simp
hence "(h a) ⊗⇘S⇙ (h b) = 𝟬⇘S⇙" using a b by simp
hence "h a = 𝟬⇘S⇙ ∨ h b = 𝟬⇘S⇙" using a b domain.integral[OF A] by simp
thus "a = 𝟬 ∨ b = 𝟬"
using a b assms unfolding inj_on_def by force
qed
qed
end